Madhukadi Agada in Lutha Visha Cikitsa - Seemaja G; Arya P (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra is a specialised branch of Ayurveda that deals with study of poisons, their effects on human body and their management. The principles of Agadatantra provide a framework for understanding and managing venomous bites in general. In Ayurveda, Visha is classified as Sthavara and Jangama visha. Lutha visha is one among the Jangama Visha. Identification and treatment of Lutha visha is an important task as improper handling of the cases may worsen the condition. Madhukadi Agada is a formulation mentioned in the context of Lutha visha, explained in Caraka Samhitha, Visha Cikitsa Adhyaya. The formulation comprises eight ingredients and can be administered as Panam (internal administration) with honey. This paper attempts to review the formulation Madhukadi Agada and to analyse its usefulness in similar conditions.